Dialek Quraisy dalam Perspektif Fiqhul Lughah : Dominasi Linguistik dan Pembentukan Bahasa Arab Baku (International Forum of Researchers and Lecturers, 2025)
The Quraysh dialect is one of the Arabic language variants that has played a significant role in the formation of Standard Arabic. This dialect became dominant during the pre-Islamic era and remained influential after the spread of Islam, particularly as it was used in the codification of the Qur’an. This study aims to examine the role of the Quraysh dialect in shaping Standard Arabic from the perspective of Fiqh al-Lughah and to analyze the linguistic and social factors that contributed to its dominance. This research employs a qualitative method with a historical linguistic and sociolinguistic approach. Data is collected from various sources discussing the historical development of Arabic, the codification of the Qur’an, and the social factors influencing the spread of the Quraysh dialect. The findings indicate that the Quraysh dialect possessed advantages in phonology, morphology, and syntax, making it superior to other Arabic dialects. Additionally, social factors such as the Quraysh tribe’s role in trade, politics, and religion further solidified its position as the standard language. The implications of this study emphasize that the Quraysh dialect not only influenced the development of Standard Arabic but also contributed to the broader linguistic framework of Islamic scholarship. This research is expected to provide insights into Fiqh al-Lughah, particularly in understanding the standardization process of Arabic and the socio-cultural influences on its evolution.